Comparison of Retzius-Sparing Robot-Assisted Radical Prostatectomy vs. Conventional Robot-Assisted Radical Prostatectomy: An Up-to-Date Meta-Analysis - Xu, Jiang-Nan; Xu, Zhen-Yu; Yin, Hu-Ming (Frontiers in Surgery, 2021)
Background: The Retzius space-sparing robot-assisted radical prostatectomy (RS-RARP) has shown better results in urinary continence, but its efficacy and safety compared to conventional robot-assisted radical prostatectomy (c-RARP) remain controversial. Material and Methods: A research was conducted in Medline via PubMed, Cochrane Library, EMBASE, and Web of Science up to January 4, 2021, to identify studies comparing RS-RARP to c-RARP. We used RevMan 5.3 and STATA 14.0 for meta-analysis. Results: A total of 14 studies involving 3,129 participants were included. Meta-analysis showed no significant difference in positive surgical margins (PSMs), but the RS-RARP group had significantly higher PSM rates in the anterior site [odds ratio (OR) = 2.25, 95% CI: 1.22–4.16, P = 0.01]. Postoperative continence in RS-RARP group at 1 month (OR = 5.72, 95% CI: 3.56–9.19, P < 0.01), 3 months (OR = 6.44, 95% CI: 4.50–9.22, P < 0.01), 6 months (OR = 8.68, 95% CI: 4.01–18.82, P < 0.01), and 12 months (OR = 2.37, 95% CI: 1.20–4.70, P = 0.01) was significantly better than that in the c-RARP group. In addition, the RS-RARP group had a shorter console time (mean difference = −16.28, 95% CI: −27.04 to −5.53, P = 0.003) and a lower incidence of hernia (OR = 0.35, 95% CI: 0.19–0.67, P = 0.001). However, there were no significant differences in estimated blood loss, pelvic lymph node dissection rate, postoperative complications, 1-year-biochemical recurrence rate, and postoperative sexual function. Conclusions: Compared with c-RARP, RS-RARP showed better recovery of continence, shorter console time, and lower incidence of hernia. Although there was no significant difference in overall PSM, we suggest that the surgeon should be more careful if the lesion is in the anterior prostate.